Byte by byte: Policy innovation for transforming Africa’s food system with digital technologies - Malabo Montpellier Panel (International Food Policy Research Institute, 2019)
Africa’s digital transformation is underway, creating opportunities for the continent to leverage the potential benefits of digitalization for agriculture, particularly smallholder farmers. This report looks at seven African countries on the forefront of progress in digitalization of the agriculture sector, analyzing the role of institutional and policy innovations as well as private sector actions that increase farmers’ access to information, services, and markets using digital tools. Numerous examples shed light on what works and what does not. The case study analysis—covering Côte d’Ivoire, Ghana, Kenya, Morocco, Nigeria, Rwanda, and Senegal—supports recommendations for public and private sector innovations to foster digitalization for growth and competitiveness in Africa’s agricultural value chains.